Organic light-emitting material and application thereof

CN122978151APending Publication Date: 2026-10-27JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510536251.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

基于硼氮共振骨架的TADF材料具有高效率和窄谱带发射特性,但是由于其共振共轭骨架的平面性,导致其聚集淬灭效应严重,电致发光器件的驱动电压高,稳定性差等问题

Benefits of technology

[0070]一方面,本发明中由于具有空间立体构型的金刚烷基团的引入抑制了分子间的相互作用,提高了器件效率与稳定性。由本发明提供的有机电致发光组合物作为发光层材料制备的电致发光器件不仅实现了窄光谱发射,并且使器件的电致发光外量子效率超过24%,器件寿命在50小时以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978151A_ABST
    Figure CN122978151A_ABST
Patent Text Reader

Abstract

The application provides an organic light-emitting material and application thereof, and the organic light-emitting material is a compound with a structure shown in formula I, formula II or formula III. The organic light-emitting material has obvious technical advantages in aspects of device driving voltage, device efficiency and device life. An electroluminescent device prepared from the compound with the structure shown in formula I, formula II or formula III has good color purity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic electroluminescence technology, and relates to an organic light-emitting material and its application. Background Technology

[0002] Organic optoelectronic materials are a class of organic materials that possess properties such as the generation, conversion, and transport of photons and electrons. Currently, the controllable optoelectronic properties of organic optoelectronic materials have been applied to organic light-emitting diodes (OLEDs), organic solar cells (OPVs), organic field-effect transistors (OFETs), and even organic lasers. In recent years, OLEDs have become a very popular new type of flat panel display product both domestically and internationally. OLED displays feature self-emissive characteristics, wide viewing angle, short response time, high luminous efficiency, wide color gamut, low operating voltage, thin panels, the ability to fabricate large-size flexible panels, and low cost.

[0003] The history of organic electroluminescence can be traced back to the report by Bernanose et al. in 1953 (Holst GA, Kster T, Voges E, et al. FLOX—an oxygen-flux-measuring system using a phase-modulation method to evaluate the oxygen-dependent fluorescence lifetime, ScienceDirect. Sensors and Actuators B: Chemical, 1995, 29, 213.). About 10 years later, in 1963, Pope et al. of New York University observed the fluorescence emission of anthracene by applying a voltage to anthracene crystals (M. Pope, H. Kallmann and P. Magnante, Electroluminescence in Organic Crystals, J. Chem. Phys., 1963, 38, 2042). In 1987, CWTang et al. of Kodak Corporation in the United States used ultrathin film technology, employing aromatic amines with good hole transport performance as the hole transport layer, an aluminum complex of 8-hydroxyquinoline as the light-emitting layer, and indium tin oxide (ITO) thin film and a metal alloy as the anode and cathode, respectively, to fabricate a light-emitting device. This device achieved a brightness of 1000 cd / m² at a driving voltage of 10V. 2The green light emission of the device, with an efficiency of 1.5 lm / W (CWTang and S.A. Van Slyke, Organic electroluminescent diodes, Appl. Phys. Lett., 1987, 51, 913), was a breakthrough that led to the rapid and in-depth development of organic electroluminescence research worldwide. In 1990, Burroughes et al. of Cambridge University proposed the first light-emitting diode based on polymer (PPV). This showed that PPV, in monolayer devices, can serve as a highly fluorescent emitting material with high luminous efficiency (Burroughes J He et al., Light-emitting diodes based on conjugated polymers, Nature, 1990, 347, 539). In 1998, Baldo and Forrest et al. from Princeton University reported the first phosphorescent device based on electroluminescence, which in principle could have 100% internal quantum yield (MA Baldo, DFO' Brinetal., Highly efficient phosphorescent emission from organic electroluminescent devices, Nature, 1998, 395, 151). However, on the one hand, phosphorescent materials generally use precious metals such as iridium and platinum, which are expensive. On the other hand, deep blue phosphorescent materials still have chemical instability and large efficiency roll-off problems at high current densities. Therefore, it is extremely important to develop an OLED device that can achieve high-efficiency light emission using inexpensive and stable small organic molecule materials.

[0004] In 2012, the Adachi research group at Kyushu University reported a highly efficient all-fluorescent OLED device based on the thermally activated delayed fluorescence (TADF) mechanism (Uoyama H, Goushi K, Shizu K, et al. Highly efficient organic light-emitting diodes from delayed fluorescence, Nature, 2012, 492(7428):234-238.). When the energy difference between the S1 and T1 levels of a molecule is sufficiently small, the triplet exciton can absorb thermal energy, return to the singlet state through a RISC process, and then emit fluorescence. Theoretically, the internal quantum efficiency (IQE) of this device can reach 100%, and the external quantum efficiency (EQE) can even reach 30%, comparable to the level of phosphorescent devices. As a next-generation light-emitting material, research on TADF materials is booming.

[0005] TADF molecules are mainly used as guest materials to dope in wide-bandgap host materials to achieve high-efficiency thermally activated delayed fluorescence (Q. Zhang, J. Li, K. Shizu, et al. Design of Efficient Thermally Activated Delayed Fluorescence Materials for Pure Blue Organic Light Emitting Diodes, J. Am. Chem. Soc. 2012, 134, 14706; H. Uoyama, K. Goushi, K. Shizu, H. Nomura, C. Adachi, Highly efficient organic light-emitting diodes from delayed fluorescence, Nature, 2012, 492, 234; T. Nishimoto, T. Yasuda, et al. Asix-carbazole-decorated cyclophosphazene as a host with high triplet energy to realize efficient delayed-fluorescence OLEDs, Mater. Horiz. 2014, 1, 264). Unlike traditional localized (LE) state luminescence in fluorescent molecules, TADF emission primarily originates from transitions between ICT states. Therefore, it is easily affected by vibrational and rotational motions between donor and acceptor states, resulting in lower electroluminescence efficiency and poor stability. Thus, the research and development of high-efficiency and high-stability TADF materials is essential. TADF materials based on a boron-nitrogen resonance framework possess high efficiency and narrow-band emission characteristics; however, due to the planarity of its resonant conjugated framework, they suffer from severe aggregation quenching effects, leading to high driving voltages and poor stability in electroluminescent devices. Therefore, developing high-efficiency and high-stability narrow-band luminescent materials based on a boron-nitrogen resonance framework is a crucial high-performance material urgently needed for OLED display technology. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide an organic light-emitting material, its preparation method and application. The organic light-emitting material of this invention is a high-efficiency, long-life narrow-spectrum electroluminescent blue light material.

[0007] To achieve this objective, the present invention adopts the following technical solution:

[0008] On the one hand, the present invention provides an organic light-emitting material, wherein the organic light-emitting material is a compound having the structure shown in Formula I, Formula II or Formula III;

[0009]

[0010] Ring A represents the following group II-A:

[0011]

[0012] Ring B represents the following groups: III-B1, III-B2, or III-B3:

[0013]

[0014] X is an O, S, or Se atom;

[0015] R is selected from C1-C8 alkyl, C6-C18 aryl, or surrounded by one or more R. a Substituted C6-C18 aryl, 5- to 18-heteroaryl, and substituted with one or more R a Substituted 5- to 18-membered heteroaryl groups;

[0016] R 1 R 2 R 3 R 4 R 5 R 6 R 7 R 8 R 9 and R 10 Independently selected from H, deuterium, C1-C8 alkyl, C6-C18 aryl, and surrounded by one or more R a Substituted C6-C18 aryl, 5- to 18-heteroaryl, and substituted with one or more R a Substituted 5- to 18-membered heteroaryl groups;

[0017] R 1 R 2 R 3 R 4 R 5 R 6 R 7 R 8 R 9 and R 10 Independent existence or R 1 R 2 R 3 R 4 R 5 R 6 R 7 R 8 R 9 and R 10 At least one of them forms a ring with the connected aromatic ring;

[0018] R 11 R 12 and R 13 It is independently selected from H, deuterium, C1-C8 alkyl, C1-C8 alkoxy, C6-C18 aryl or 5- to 18-heteroaryl;

[0019] R a Each time it appears, it is independently deuterium, fluorine, C1-C12 alkyl, C1-C12 alkoxy, or C6-C18 aryl.

[0020] * indicates the linking site of a functional group.

[0021] Preferably, R 1 R 2 R 3 R 4 R 5 R 6 R 7 R 8 R 9 and R 10 Independently selected from hydrogen, C3-C6 alkyl, C6-C14 aryl, and surrounded by one or more R a Substituted C6-C18 aryl, 5- to 18-heteroaryl, and substituted with one or more R a Substituted 5- to 18-membered heteroaryl groups;

[0022] Preferably, R 1 R 2 R 3 R 4 R 5 R 6 R 7 and R 8 Independently selected from hydrogen, tert-butyl, phenyl, biphenyl, methyl-substituted biphenyl, cyclohexyl, adamantyl, terphenyl,

[0023] * indicates the linking site of a functional group;

[0024] Preferably, the biphenyl is selected from...

[0025] Preferably, the terphenyl group is selected from...

[0026] * indicates the linking site of a functional group.

[0027] More preferably, R 1 R 2 R 3 R 4 R 5 R6 R 7 and R 8 It is independently selected from hydrogen, tert-butyl or phenyl.

[0028] Preferably, the R 9 R 10 R 11 R 12 and R 13 Selected independently from H.

[0029] Preferably, X is S.

[0030] Preferably, A is selected from Preferably, B is selected from Preferably, R is selected from tert-butyl, phenyl, More preferably, R is selected from tert-butyl or phenyl.

[0031] In one embodiment of the present invention, the organic light-emitting material is any one of the compounds of formula BN-1 to BN-76:

[0032]

[0033]

[0034]

[0035]

[0036]

[0037] On the other hand, the present invention provides an organic electroluminescent composition comprising at least one of the above-mentioned organic light-emitting materials and a host material, wherein the host material is at least one of the following compounds or compounds in which all or part of the hydrogen atoms are deuterated:

[0038]

[0039]

[0040]

[0041] Preferably, the doping ratio of the organic light-emitting material in the organic electroluminescent composition is 0.5 to 30 wt% (mass ratio), for example, 0.5 wt%, 0.8 wt%, 1 wt%, 3 wt%, 5 wt%, 10 wt%, 15 wt%, 18 wt%, 20 wt%, 25 wt%, or 30 wt%.

[0042] Preferably, the organic electroluminescent composition contains a compound of formula TS as a sensitizer.

[0043]

[0044] R S1 R S2 R S3 and R S4 It is independently selected from H, deuterium, C1-C8 alkyl or C6-C18 aryl.

[0045] Preferably, the doping ratio of the sensitizer in the organic electroluminescent composition is 5.0 to 30.0 wt%, for example, 0.5 wt%, 0.8 wt%, 1 wt%, 3 wt%, 5 wt%, 10 wt%, 15 wt%, 18 wt%, 20 wt%, 25 wt%, or 30 wt%.

[0046] On the other hand, the present invention provides an organic electroluminescent device comprising the organic light-emitting material as described above or the organic electroluminescent composition as described above.

[0047] Preferably, the organic electroluminescent device includes a substrate, and an anode layer, an organic light-emitting functional layer, and a cathode layer sequentially formed on the substrate; the organic light-emitting functional layer includes a light-emitting layer, which contains the organic light-emitting material as described above or the organic electroluminescent composition as described above.

[0048] Preferably, the organic light-emitting functional layer further includes any one or a combination of at least two of the following: a hole injection layer, a hole transport layer, an electron blocking layer, a hole blocking layer, an electron transport layer, and an electron injection layer.

[0049] On the other hand, the present invention provides an application of the described organic electroluminescent device in an organic electroluminescent display or an organic electroluminescent lighting source.

[0050] Terminology Explanation

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0052] As used herein, the terms “containing” or “including (comprise)” can be open-ended, semi-closed, or closed. In other words, the terms also include “consistently made of” or “made of”.

[0053] Group definition

[0054] In this specification, groups and their substituents may be selected by those skilled in the art to provide stable structural moieties and compounds. When a substituent is described by a conventional chemical formula written from left to right, the substituent also includes chemically equivalent substituents obtained when the structural formula is written from right to left.

[0055] The section headings used in this specification are for organizational purposes only and should not be construed as limiting the subject matter. All references or portions thereof cited in this invention, including but not limited to patents, patent applications, articles, books, user manuals, and papers, are incorporated herein by reference in their entirety.

[0056] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter pertains. Where multiple definitions exist for a term, the definition herein shall prevail.

[0057] It should be understood that the singular forms used in this invention, such as "a," include plural references unless otherwise specified. Furthermore, the term "comprising" is an open-ended limitation, not a closed one; that is, it includes the contents specified in this invention but does not exclude other aspects.

[0058] Unless otherwise stated, this invention employs traditional methods of mass spectrometry and elemental analysis, and the steps and conditions can be referred to conventional operating procedures and conditions in the field.

[0059] Unless otherwise specified, this invention employs standard nomenclature and standard laboratory procedures and techniques of analytical chemistry, organic synthetic chemistry, and optics. In some cases, standard techniques are used for chemical synthesis, chemical analysis, and performance testing of light-emitting devices.

[0060] The compounds of the present invention may contain atomic isotopes in non-natural proportions on one or more atoms constituting the compound. For example, the compounds may be labeled with radioactive isotopes, such as deuterium (₂H). All variations in the isotopic composition of the compounds of the present invention, regardless of radioactivity, are included within the scope of the present invention.

[0061] In this invention, unless otherwise specified, the number of "substitutes" can be one or more; when there are multiples, it means two or more, such as two, three, or four. Furthermore, when there are multiple "substitutes," the "substitutes" can be the same or different. In this invention, unless otherwise specified, the position of the "substitute" can be arbitrary.

[0062] In this invention, as a group or part of other groups (e.g., in halogen-substituted alkyl groups), the term "alkyl" means a saturated aliphatic hydrocarbon group comprising branched and straight chains having a specified number of carbon atoms. For example, C1-C1... 20Alkyl groups include straight-chain or branched alkyl groups having 1 to 20 carbon atoms. As defined in "C1-C6 alkyl," it includes groups having 1, 2, 3, 4, 5, or 6 carbon atoms in a straight-chain or branched structure. For example, in this invention, each of the C1-C6 alkyl groups is independently methyl, ethyl, propyl, butyl, pentyl, or hexyl; wherein, propyl is a C3 alkyl group (including isomers, such as n-propyl or isopropyl); butyl is a C4 alkyl group (including isomers, such as n-butyl, sec-butyl, isobutyl, or tert-butyl); pentyl is a C5 alkyl group (including isomers, such as n-pentyl, 1-methyl-butyl, 1-ethyl-propyl, 2-methyl-1-butyl, 3-methyl-1-butyl, isopentyl, tert-pentyl, or neopentyl); and hexyl is a C6 alkyl group (including isomers, such as n-hexyl or isohexyl).

[0063] As used herein, the term "alkoxy" refers to an alkyl group as defined above, which is connected via an oxygen bond (-O-).

[0064] In this invention, as a group or part of other groups, the term "Cn-m aryl" refers to a monocyclic or polycyclic aromatic group (with only carbon atoms as ring atoms) having n to m ring carbon atoms, possessing at least one carbon ring with a conjugated π-electron system. Examples of the aforementioned aryl unit include phenyl, naphthyl, indene, azulel, fluorenyl, phenanthryl, or anthraceneyl. In one embodiment, the aryl group is preferably a C6-14 aryl group, such as phenyl and naphthyl, more preferably phenyl.

[0065] In this invention, as a group or part of other groups, the term "nm-aryl" refers to an aromatic group whose ring atoms comprise one or more (e.g., 1, 2, 3, and 4) heteroatoms selected from nitrogen, oxygen, and sulfur, having n to m ring atoms. The heteroaryl group is a monocyclic, bicyclic, tricyclic, or tetracyclic system, wherein at least one ring is an aromatic ring. Heteroaryl groups within this definition include, but are not limited to: acridinel, carbazolyl, cyclophosphinyl, quinoxalinyl, pyrazolyl, indolyl, benzotriazolyl, furanyl, thiophene, benzothiophene, benzofuranyl, quinolinyl, isoquinolinyl, oxazolyl, isoxazolyl, pyrazinyl, pyridinyl, pyrimidinel, pyrroleyl, tetrahydroquinoline, imidazolyl, triazolyl, tetrazolyl, thiazolyl, isothiazolyl, furazolyl, thiadiazolyl, etc. Oxadiazole, pyridinyl, pyrazinyl, pyridazinyl, pyrimidinyl, triazinyl, purine, pteridinyl, naphridinyl, quinazolinyl, phthalazinyl, imidazopyridinyl, imidazothiazolyl, imidazooxazinyl, benzothiazolyl, benzooxazinyl, benzoimidazolyl, isoindolyl, indazole, pyrrolopyridinyl, thienopyridinyl, furanolopyridinyl, benzothiadiazole, benzooxadiazole, pyrrolopyrimidinyl, thienofuranyl. In one embodiment, as preferred examples of "5- to 18-membered heteroaryl groups", furanyl, thienoyl, pyrrololyl, imidazolyl, thiazolyl, pyrazolyl, oxazolyl, isoxazolyl, isothiazolyl, pyridinyl, pyrimidinyl, and carbazoleyl are listed, more preferably carbazoleyl.

[0066] As used herein, the term Cn-Cm cycloalkyl refers to a monocyclic or polycyclic alkyl group having n to m carbon atoms, such as C3-C10 and C3-C6 cycloalkyl groups. Examples include adamantyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and dicycloheptyl. In one embodiment, the C3-C10 cycloalkyl group is preferably adamantyl or cyclohexyl.

[0067] In this invention, the defined carbon number range of a group refers to any integer number of carbon atoms included within the defined range. For example, C1 to C8 means that the number of carbon atoms in the group can be 1, 2, 3, 4, 5, 6, 7 or 8, and C6 to C18 means that the number of carbon atoms in the group can be 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17 or 18. The defined carbon number range of other groups is similar.

[0068] Without violating common sense in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.

[0069] Compared with the prior art, the present invention has the following beneficial effects:

[0070] On the one hand, the introduction of adamantyl groups with a spatial stereochemical configuration in this invention suppresses intermolecular interactions, thereby improving device efficiency and stability. Electroluminescent devices prepared using the organic electroluminescent composition provided by this invention as the emitting layer material not only achieve narrow-spectrum emission but also achieve an external quantum efficiency exceeding 24% and a device lifetime of over 50 hours. Attached Figure Description

[0071] Figure 1 This is a schematic diagram of the structure of the vacuum evaporation type organic electroluminescent device provided by the present invention, wherein 1 is the ITO anode, 2 is the hole injection layer, 3 is the first hole transport layer, 4 is the second hole transport layer, 5 is the light-emitting layer, 6 is the first electron transport layer, 7 is the second electron transport layer, 8 is the electron injection layer, and 9 is the metal cathode.

[0072] Figure 2 The electroluminescence spectrum of the BN-1 based device is shown. Detailed Implementation

[0073] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.

[0074] The raw materials used in the synthesis of the compound are:

[0075] Raw material A:

[0076]

[0077] Raw material B:

[0078]

[0079] Raw material C:

[0080]

[0081] Raw material D:

[0082]

[0083] Raw material E:

[0084]

[0085] Synthesis experiment of representative compound BN-1:

[0086]

[0087] Synthesis and characterization of compound BN-1-A: Starting material A-1 (24.9 g, 100.0 mmol), starting material B-1 (24.3 g, 100.0 mmol), and scandium trifluoroformate (2.0 g, 4.0 mmol) were dissolved in 500 mL of dry dichloromethane. The mixture was heated to reflux and stirred continuously for 6 hours. After the reaction was completed and cooled to room temperature, the solution was recrystallized from dichloromethane / methanol through a silica gel funnel to give 41.6 g of a white solid, with a yield of 90.6%. Mass spectrometry analysis confirmed the product as BN-1-A, MS: 459.26 (calculated value: 459.02).

[0088] Synthesis and characterization of compound BN-1-B: Copper chloride (5.7 g, 140.0 mmol) and tert-butyl nitrite (10.8 g, 105.0 mmol) were dissolved in 500 mL of acetonitrile. A 200 mL acetonitrile solution of compound BN-1-A (32.1 g, 70.0 mmol) was added dropwise to the above system, and the mixture was heated to 50 °C and stirred for 4 hours. After the reaction was completed, the solvent was removed under reduced pressure, and the solution was passed through a silica gel funnel using petroleum ether. The solvent was then evaporated to dryness and dried to obtain 30.7 g of a white solid, with a yield of 91.7%. Mass spectrometry analysis confirmed the product as BN-1-B, MS: 478.19 (calculated value: 477.97).

[0089] Synthesis and characterization of compound BN-1-C: Compound BN-1-B (26.3 g, 55.0 mmol), starting material C-1 (34.1 g, 121 mmol), and sodium tert-butoxide (15.8 g, 165.0 mmol) were dissolved in 300 mL of toluene. Palladium acetate (370.0 mg, 1.6 mmol) and tri-tert-butylphosphine (646.0 mg, 3.2 mmol) were added under nitrogen atmosphere. The mixture was heated to 100 °C and stirred continuously for 12 hours. After the reaction was completed and cooled to room temperature, the reaction system was washed with dichloromethane and water. The organic phase was concentrated and purified by column chromatography to give 45.1 g of white solid, with a yield of 93.1%. Mass spectrometry analysis confirmed it to be the target product BN-1-C, MS: 880.21 (calculated value: 880.55).

[0090] Synthesis and characterization of compound BN-1: Compound BN-1-C (35.2 g, 40.0 mmol) was dissolved in 150 mL of tert-butylbenzene. Tert-butyllithium (36.9 mL, 48.0 mmol, 1.3 M) was added dropwise at 0 °C under nitrogen atmosphere. After lithiation at 60 °C for 2 hours, the temperature was lowered to 0 °C, and BBr3 (15.1 g, 60 mmol) was added dropwise. The mixture was then heated to room temperature and stirred for 1 hour. After cooling to 0 °C, N,N-diisopropylethylamine (DIEA) (10.4 g, 80.0 mmol) was added dropwise. The temperature was then raised to 120 °C and stirred continuously for 8 hours. After the reaction was complete and cooled to room temperature, the reaction was quenched with 10 mL each of methanol and water. The reaction system was washed three times each with 200 mL of dichloromethane and water. The organic phase was concentrated and purified by column chromatography (evolving solvent: dichloromethane / petroleum ether = 1:9) to give 13.3 g of a pale yellow solid (yield 39.0%). Mass spectrometry and elemental analysis confirmed it as the target product: MS: 854.21 (calculated: 854.57); elemental analysis: C, 87.13; H, 8.31; N, 3.33 (calculated: C, 87.09; H, 8.37; B, 1.26; N, 3.28). Synthesis of the representative compound BN-4:

[0091]

[0092] Synthesis and characterization of compound BN-4-A: Starting material A-2 (20.5 g, 100.0 mmol), starting material B (24.3 g, 100.0 mmol), and scandium trifluoroformate (4.0 g, 8.0 mmol) were dissolved in 500 mL of dry dichloromethane. The mixture was heated to reflux and stirred continuously for 6 hours. After the reaction was completed and cooled to room temperature, the solution was recrystallized from dichloromethane / methanol using a silica gel funnel to give 38.2 g of a white solid, with a yield of 92.1%. Mass spectrometry analysis confirmed the product as BN-4-A, MS: 415.31 (calculated value: 415.07).

[0093] Synthesis and characterization of compound BN-4-B: Copper chloride (5.7 g, 140.0 mmol) and tert-butyl nitrite (10.8 g, 105.0 mmol) were dissolved in 500 mL of acetonitrile. A 200 mL acetonitrile solution of compound BN-1-A (29.1 g, 70.0 mmol) was added dropwise to the above system. The mixture was heated to 50 °C and stirred for 4 hours. After the reaction was complete, the solvent was removed under reduced pressure, and the solution was passed through a silica gel funnel using petroleum ether. The solvent was then evaporated to dryness and dried to obtain 24.2 g of a white solid, with a yield of 79.5%. Mass spectrometry analysis confirmed the product as BN-4-B, MS: 434.18 (calculated value: 434.02).

[0094] Synthesis and characterization of compound BN-4-C: Compound BN-4-B (23.9 g, 55.0 mmol), starting material C-1 (16.9 g, 60.0 mmol), and sodium tert-butoxide (7.9 g, 82.5 mmol) were dissolved in 300 mL of toluene. Palladium acetate (370.0 mg, 1.6 mmol) and tri-tert-butylphosphine (646.0 mg, 3.2 mmol) were added under nitrogen atmosphere. The mixture was heated to 100 °C and stirred continuously for 12 hours. After the reaction was completed and cooled to room temperature, the reaction system was washed with dichloromethane and water. The organic phase was concentrated and purified by column chromatography to give 31.9 g of white solid, with a yield of 91.3%. Mass spectrometry analysis confirmed it to be the target product BN-4-C, MS: 636.89 (calculated value: 636.74).

[0095] Synthesis and characterization of compound BN-4-D: Compound BN-4-C (25.4 g, 40.0 mmol), starting material C-2 (18.1 g, 60.0 mmol), and sodium tert-butoxide (7.7 g, 80.0 mmol) were dissolved in 250 mL of toluene. (AMPHOS)PdCl2 (1.6 g, 2.2 mmol) was added under nitrogen atmosphere. The mixture was heated to 100 °C and stirred continuously for 12 hours. After the reaction was complete and cooled to room temperature, the reaction system was washed with dichloromethane and water. The organic phase was concentrated and purified by column chromatography to give 30.1 g of a white solid, with a yield of 83.4%. Mass spectrometry analysis confirmed it to be the target product BN-4-D, MS: 900.17 (calculated value: 900.51).

[0096] Synthesis and characterization of compound BN-4: Compound BN-4-D (27.0 g, 30.0 mmol) was dissolved in 100 mL of tert-butylbenzene. Tert-butyllithium (27.7 mL, 36.0 mmol, 1.3 M) was added dropwise at 0 °C under nitrogen atmosphere. After lithiation at 60 °C for 2 hours, the temperature was lowered to 0 °C, and BBr3 (11.2 g, 45.0 mmol) was added dropwise. The temperature was raised to room temperature and stirred for 1 hour. The temperature was then lowered to 0 °C, and N,N-diisopropylethylamine (DIEA) (5.8 g, 45.0 mmol) was added dropwise. The temperature was raised to 120 °C and stirred continuously for 8 hours. After the reaction was complete and cooled to room temperature, the reaction was quenched with 10 mL each of methanol and water. The reaction system was washed three times each with 200 mL of dichloromethane and water. The organic phase was concentrated and purified by column chromatography (evolving solvent: dichloromethane / petroleum ether = 1:9) to give 7.6 g of a pale yellow solid (yield 29.0%). Mass spectrometry and elemental analysis confirmed it as the target product: MS: 874.68 (calculated: 874.54); elemental analysis: C, 87.80; H, 7.83; N, 3.13 (calculated: C, 87.85; H, 7.72; B, 1.24; N, 3.20). Synthesis of the representative compound BN-13:

[0097]

[0098] Synthesis and characterization of compound BN-13-A: Starting material A-2 (20.5 g, 100.0 mmol), starting material B (24.3 g, 100.0 mmol), and scandium trifluoroformate (4.0 g, 8.0 mmol) were dissolved in 500 mL of dry dichloromethane. The mixture was heated to reflux and stirred continuously for 6 hours. After the reaction was complete and cooled to room temperature, the solution was recrystallized from dichloromethane / methanol using a silica gel funnel to give 38.2 g of a white solid, with a yield of 92.1%. Mass spectrometry analysis confirmed the product as BN-13-A (MS: 415.31, calculated value: 415.07).

[0099] Synthesis and characterization of compound BN-13-B: Copper chloride (5.7 g, 140.0 mmol) and tert-butyl nitrite (10.8 g, 105.0 mmol) were dissolved in 500 mL of acetonitrile. A 200 mL acetonitrile solution of compound BN-13-A (29.1 g, 70.0 mmol) was added dropwise to the above system. The mixture was heated to 50 °C and stirred for 4 hours. After the reaction was completed, the solvent was removed under reduced pressure, and the solution was passed through a silica gel funnel using petroleum ether. The solvent was then evaporated to dryness and dried to obtain 24.2 g of a white solid, with a yield of 79.5%. Mass spectrometry analysis confirmed the product as BN-13-B, MS: 434.18 (calculated value: 434.02).

[0100] Synthesis and characterization of compound BN-13-C: Compound BN-13-B (23.9 g, 55.0 mmol), starting material C-1 (16.9 g, 60.0 mmol), and sodium tert-butoxide (7.9 g, 82.5 mmol) were dissolved in 300 mL of toluene. Palladium acetate (370.0 mg, 1.6 mmol) and tri-tert-butylphosphine (646.0 mg, 3.2 mmol) were added under nitrogen atmosphere. The mixture was heated to 100 °C and stirred continuously for 12 hours. After the reaction was completed and cooled to room temperature, the reaction system was washed with dichloromethane and water. The organic phase was concentrated and purified by column chromatography to give 31.9 g of white solid, with a yield of 91.3%. Mass spectrometry analysis confirmed it to be the target product BN-13-C, MS: 636.89 (calculated value: 636.74).

[0101] Synthesis and characterization of compound BN-13-D: Compound BN-13-C (25.4 g, 40.0 mmol), starting material C-5 (20.2 g, 60.0 mmol), and sodium tert-butoxide (7.7 g, 80.0 mmol) were dissolved in 250 mL of toluene. PdCl2 (1.6 g, 2.2 mmol) was added under nitrogen atmosphere. The mixture was heated to 100 °C and stirred continuously for 12 hours. After the reaction was complete and cooled to room temperature, the reaction system was washed with dichloromethane and water. The organic phase was concentrated and purified by column chromatography to give 34.3 g of a white solid, with a yield of 91.6%. Mass spectrometry analysis confirmed it to be the target product BN-13-D, MS: 936.76 (calculated value: 936.52).

[0102] Synthesis and characterization of compound BN-4: Compound BN-13-D (28.1 g, 30.0 mmol) was dissolved in 100 mL of tert-butylbenzene. Tert-butyllithium (27.7 mL, 36.0 mmol, 1.3 M) was added dropwise at 0 °C under nitrogen atmosphere. After lithiation at 60 °C for 2 hours, the temperature was lowered to 0 °C, and BBr3 (11.2 g, 45.0 mmol) was added dropwise. The temperature was raised to room temperature and stirred for 1 hour. The temperature was then lowered to 0 °C, and N,N-diisopropylethylamine (DIEA) (5.8 g, 45.0 mmol) was added dropwise. The temperature was raised to 120 °C and stirred continuously for 8 hours. After the reaction was complete and cooled to room temperature, the reaction was quenched with 10 mL each of methanol and water. The reaction system was washed three times each with 200 mL of dichloromethane and water. The organic phase was concentrated and purified by column chromatography (evolving solvent: dichloromethane / petroleum ether = 1:9) to give 9.9 g of a pale yellow solid (yield 35.2%). Mass spectrometry and elemental analysis confirmed it as the target product: MS: 936.41 (calculated value: 936.52); elemental analysis: C, 84.21; H, 7.66; N, 3.21; S, 3.39 (calculated values: C, 84.37; H, 7.58; B, 1.19; N, 3.07; S, 3.52).

[0103] Synthesis experiment of representative compound BN-61:

[0104]

[0105] Synthesis and characterization of compound BN-61-A: Starting materials D-1 (15.0 g, 73.1 mmol), E-1 (26.7 g, 73.1 mmol), and sodium tert-butoxide (14.3 g, 146.2 mmol) were dissolved in 500 mL of dry toluene. Tris(2,3-benzylacetone) dipalladium (1.37 g, 1.5 mmol) and tri-tert-butylphosphine (605.6 mg, 3.0 mmol) were added under nitrogen atmosphere. The mixture was heated to reflux and stirred continuously for 12 hours. After the reaction was completed and cooled to room temperature, the reaction system was washed with dichloromethane and water. The organic phase was concentrated and purified by column chromatography to give 30.2 g of a white solid, with a yield of 84.4%. Mass spectrometry analysis confirmed it to be the target product BN-61-A, MS: 489.80 (calculated value: 489.75).

[0106]

[0107] Synthesis and characterization of compound BN-61-B: Copper chloride (5.7 g, 140.0 mmol) and tert-butyl nitrite (10.8 g, 105.0 mmol) were dissolved in 500 mL of acetonitrile. A 200 mL acetonitrile solution of starting material A-3 (21.3 g, 70.0 mmol) was added dropwise to the above system, and the mixture was heated to 50 °C and stirred for 4 hours. After the reaction was completed, the solvent was removed under reduced pressure, and the solution was passed through a silica gel funnel using petroleum ether. The solvent was then evaporated to dryness and dried to obtain 16.3 g of a white solid, with a yield of 72.0%. Mass spectrometry analysis confirmed the product as BN-61-B, MS: 326.06 (calculated value: 326.46).

[0108] Synthesis and characterization of compound BN-61-C: Compound BN-1-B (17.9 g, 55.0 mmol), starting material C-1 (27.8 g, 82.5 mmol), and sodium tert-butoxide (15.8 g, 165.0 mmol) were dissolved in 300 mL of toluene. Palladium acetate (370.0 mg, 1.6 mmol) and tri-tert-butylphosphine (646.0 mg, 3.2 mmol) were added under nitrogen atmosphere. The mixture was heated to 100 °C and stirred continuously for 12 hours. After the reaction was completed and cooled to room temperature, the reaction system was washed with dichloromethane and water. The organic phase was concentrated and purified by column chromatography to give 21.3 g of white solid, with a yield of 73.5%. Mass spectrometry analysis confirmed it to be the target product BN-61-C, MS: 526.95 (calculated value: 527.0).

[0109] Synthesis and characterization of compound BN-61-D: Compound BN-61-C (23.7 g, 45.0 mmol), compound BN-61-A (22.0 g, 45.0 mmol), and sodium tert-butoxide (8.6 g, 90.0 mmol) were dissolved in 250 mL of toluene. (AMPHOS)PdCl2 (0.6 g, 0.9 mmol) was added under nitrogen atmosphere. The mixture was heated to 100 °C and stirred continuously for 12 hours. After the reaction was complete and cooled to room temperature, the reaction system was washed with dichloromethane and water. The organic phase was concentrated and purified by column chromatography to give 37.2 g of a white solid, with a yield of 88.4%. Mass spectrometry analysis confirmed it to be the target product BN-61-D, MS: 935.90 (calculated value: 935.82).

[0110] Synthesis and characterization of compound BN-61: Compound BN-61-D (28.1 g, 30.0 mmol) was dissolved in 100 mL of tert-butylbenzene. Tert-butyllithium (27.7 mL, 36.0 mmol, 1.3 M) was added dropwise at 0 °C under nitrogen atmosphere. After lithiation at 60 °C for 2 hours, the temperature was lowered to 0 °C, and BBr3 (11.2 g, 45.0 mmol) was added dropwise. The temperature was raised to room temperature and stirred for 1 hour. The temperature was then lowered to 0 °C, and N,N-diisopropylethylamine (DIEA) (5.8 g, 45.0 mmol) was added dropwise. The temperature was raised to 120 °C and stirred continuously for 8 hours. After the reaction was complete and cooled to room temperature, the reaction was quenched with 10 mL each of methanol and water. The reaction system was washed three times each with 200 mL of dichloromethane and water. The organic phase was concentrated and purified by column chromatography (evolving solvent: dichloromethane / petroleum ether = 1:9) to give 10.2 g of a pale yellow solid (yield 37.3%). Mass spectrometry and elemental analysis confirmed it as the target product: MS: 908.31 (calculated value: 908.62); elemental analysis: C, 87.08; H, 8.57; N, 3.01 (calculated values: C, 87.19; H, 8.54; B, 1.19; N, 3.08).

[0111] The compounds not shown in the examples below were prepared using methods similar to those described above, and the products were verified by mass spectrometry and elemental analysis, as detailed in Table 1. Mass spectrometry was performed using Bruker's Maldi-TOF (Autoflex Speed), and elemental analysis was performed using Agilent's Vario MicroCube, testing for C, H, and N.

[0112] The data from the synthesis examples are summarized in Table H1.

[0113] Table H1. Summary of data from the synthesis examples

[0114]

[0115] Examples of electroluminescent devices

[0116] The following are some representative examples of electroluminescent devices. The molecular structures of some materials involved in these device examples and comparative device examples are as follows.

[0117]

[0118]

[0119] Fabrication process of organic electroluminescent devices:

[0120] Figure 1 This is a schematic diagram of the structure of the vacuum evaporation type organic electroluminescent device provided by the present invention, wherein 1 is the ITO anode, 2 is the hole injection layer, 3 is the first hole transport layer, 4 is the second hole transport layer, 5 is the light-emitting layer, 6 is the first electron transport layer, 7 is the second electron transport layer, 8 is the electron injection layer, and 9 is the metal cathode.

[0121] The device fabrication process is as follows:

[0122] (1) Substrate treatment: Transparent ITO glass was used as the substrate material for device fabrication. It was first ultrasonically treated with 5% ITO cleaning solution for 30 minutes, then ultrasonically washed sequentially with distilled water (twice), acetone (twice), and isopropanol (twice). Finally, the ITO glass was stored in isopropanol. Before each use, the surface of the ITO glass was carefully wiped with acetone and isopropanol cotton balls, rinsed with isopropanol, dried, and then plasma-treated for 5 minutes before use.

[0123] (2) A hole injection layer (4% HI:HT-1; 50 nm), a first hole transport layer (HT-1; 50 nm), a second hole transport layer (HT-2; 5 nm), a light-emitting layer (80 wt% H-42 + 19 wt% TS + 1 wt% BN-n; 20 nm), a first electron transport layer (ET-1; 5 nm), a second electron transport layer (ET-2; 25 nm), an electron injection layer (Liq; 2 nm), and a metal cathode (Al; 100 nm) were sequentially deposited on a substrate using an evaporation process. The deposition rate of the organic material was [missing information]. The deposition rate of LiF is The deposition rate of Al is The device structure used is [ITO / 4%HI:HT-1(50nm) / HT-1(50nm) / HT-2(5nm) / 80wt%H-42+19wt%TS+1wt%BN-n(20nm) / ET-1(5nm) / ET-2(25nm) / Liq(2nm) / Al(100nm)].

[0124] The organic electroluminescent device (structure as shown in the comparative device embodiment Dm (m=1-14)) Figure 1 As shown), the device structure used is [ITO / 4%HI:HT-1(50nm) / HT-1(50nm) / HT-2(5nm) / 80wt%H-42+19wt%TS+1wt%Rm(20nm) / ET-1(5nm) / ET-2(25nm) / Liq(2nm) / Al(100nm)].

[0125] The device's current, voltage, luminance, and emission spectrum characteristics were simultaneously tested using a Photo Research PR 655 spectrophotometer and a Keithley K2400 digital source meter system. Performance testing was conducted at room temperature and under ambient conditions. The external quantum efficiency (EQE) of the device was calculated based on the Lambaugh distribution of emission, using current density, luminance, and electroluminescence spectrum combined with the apparent function.

[0126] Figure 2 The image shows the electroluminescence spectrum of the BN-1-based device, with an emission peak at 465 nm and a full width at half maximum (FWHM) of 28 nm.

[0127] The performance data of the device Dn embodiment are shown in Table 1. The device lifetime is defined as follows: the initial brightness of the device is 1000 cd / m². 2 When the device brightness increases from 1000 cd / m² 2 Reduced to 500 cd / m 2 The time required (T50, hours).

[0128] The performance data of the DR-m device embodiment are shown in Table D1. The device lifetime is defined as follows: the initial brightness of the device is 1000 cd / m. 2 When the device brightness increases from 1000 cd / m² 2 Reduced to 500 cd / m 2 The time required (T50, hours).

[0129] Table 1

[0130]

[0131]

[0132] Table D1

[0133]

[0134] Based on the data of the above-mentioned device embodiments (Table 1) and the data of the comparative device embodiments (Table D1), it can be seen that when the organic light-emitting material described in this invention is applied to electroluminescent devices, it shows obvious technical advantages in terms of device lifespan and other aspects.

[0135] The applicant declares that the organic light-emitting material and its application are illustrated by the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An organic light-emitting material, characterized in that, The organic light-emitting material is a compound having the structure shown in Formula I, Formula II or Formula III; Ring A represents the following group II-A: II-A Ring B represents the following groups: III-B1, III-B2, or III-B3: X is an O, S, or Se atom; R is selected from C1-C8 alkyl, C6-C18 aryl, or surrounded by one or more R. a Substituted C6-C18 aryl, 5- to 18-heteroaryl, and substituted with one or more R a Substituted 5- to 18-membered heteroaryl groups; R 1 R 2 R 3 R 4 R 5 R 6 R 7 R 8 R 9 and R 10 Independently selected from H, deuterium, C1-C8 alkyl, C6-C18 aryl, and surrounded by one or more R a Substituted C6-C18 aryl, 5- to 18-heteroaryl, and substituted with one or more R a Substituted 5- to 18-membered heteroaryl groups; R 1 R 2 R 3 R 4 R 5 R 6 R 7 R 8 R 9 and R 10 Independent existence or R 1 R 2 R 3 R 4 R 5 R 6 R 7 R 8 R 9 and R 10 At least one of them forms a ring with the connected aromatic ring; R 11 R 12 and R 13 It is independently selected from H, deuterium, C1-C8 alkyl, C1-C8 alkoxy, C6-C18 aryl or 5- to 18-heteroaryl; R a Each time it appears, it is independently deuterium, fluorine, C1-C12 alkyl, C1-C12 alkoxy, or C6-C18 aryl; * indicates the linking site of a functional group.

2. The organic light-emitting material according to claim 1, characterized in that, R 1 R 2 R 3 R 4 R 5 R 6 R 7 R 8 R 9 and R 10 Independently selected from hydrogen, C3-C6 alkyl, C6-C14 aryl, and surrounded by one or more R a Substituted C6-C18 aryl, 5- to 18-heteroaryl, and substituted with one or more R a Substituted 5- to 18-membered heteroaryl groups; Preferably, R 1 R 2 R 3 R 4 R 5 R 6 R 7 and R 8 Independently selected from hydrogen, tert-butyl, phenyl, biphenyl, methyl-substituted biphenyl, cyclohexyl, adamantyl, terphenyl, * indicates the linking site of a functional group; Preferably, the biphenyl is selected from... Preferably, the terphenyl group is selected from... * indicates the linking site of a functional group; More preferably, R 1 R 2 R 3 R 4 R 5 R 6 R 7 and R 8 It is independently selected from hydrogen, tert-butyl or phenyl.

3. The organic light-emitting material according to claim 1, characterized in that, The R 9 R 10 R 11 R 12 and R 13 Independently selected from H; Preferably, X is S; Preferably, A is selected from Preferably, B is selected from 4. The organic light-emitting material according to claim 1, characterized in that, R is selected from tert-butyl, phenyl, ... More preferably, R is selected from tert-butyl or phenyl.

5. The organic light-emitting material according to any one of claims 1-4, characterized in that, The organic light-emitting material is any one of the compounds of formula BN-1 to BN-76:

6. An organic electroluminescent composition, characterized in that, The organic electroluminescent composition comprises at least one of the organic light-emitting materials according to any one of claims 1-5 and a host material, wherein the host material is at least one of the following compounds or compounds in which all or part of the hydrogen atoms are deuterated:

7. The organic electroluminescent composition according to claim 6, characterized in that, The organic light-emitting material in the organic electroluminescent composition is doped at a ratio of 0.5 to 15.0 wt%. Preferably, the organic electroluminescent composition contains a compound of formula TS as a sensitizer. R S1 R S2 R S3 and R S4 It is independently selected from H, deuterium, C1-C8 alkyl or C6-C18 aryl; Preferably, the doping ratio of the sensitizer in the organic electroluminescent composition is 5.0 to 30.0 wt%.

8. An organic electroluminescent device, characterized in that, The organic electroluminescent device comprises the organic light-emitting material according to any one of claims 1-5 or the organic electroluminescent composition according to claim 6 or 7.

9. The organic electroluminescent device according to claim 8, characterized in that, The organic electroluminescent device includes a substrate, and an anode layer, an organic light-emitting functional layer, and a cathode layer sequentially formed on the substrate; the organic light-emitting functional layer includes a light-emitting layer, which contains the organic light-emitting material according to any one of claims 1-5 or the organic electroluminescent composition according to claim 6 or 7; Preferably, the organic light-emitting functional layer further includes any one or a combination of at least two of the following: a hole injection layer, a hole transport layer, an electron blocking layer, a hole blocking layer, an electron transport layer, and an electron injection layer.

10. The application of the organic electroluminescent device according to claim 5 in an organic electroluminescent display or an organic electroluminescent lighting source.